Neuro-ophthalmological presentation of non-invasive Aspergillus sinus disease in the non-immunocompromised host. Issue 2 (February 1994) - Brown, P; Demaerel, P; McNaught, A; Revesz, T; Graham, E; Kendall, B E; Plant, G
Abstract : Two cases of non-invasive aspergillosis of the nose and paranasal sinuses are described. The first presented with left proptosis and ophthalmoplegia. Imaging and histology showed a maxillary sinus aspergilloma. The second case presented as a compressive optic neuropathy and histology showed allergic aspergillus sinusitis. The pathological distinction between invasive and non-invasive forms of aspergillus sinusitis is important as in invasive aspergillosis surgical treatment is most effectively combined with systemic antifungal treatment, whereas in aspergilloma of the paranasal sinuses surgical drainage of the sinuses alone is usually sufficient, and in allergic aspergillus sinusitis surgery is best combined with systemic or topical steroids. The distinction between invasive and non-invasive forms is particularly important as both may present with cranial neuropathies.